FOREST POLICY AND LEGAL PLURALISM: A CASE STUDY IN LUWU DISTRICT, INDONESIA - Wibowo, Lukas Rumboko; Murdiati, C. Woro; Race, Digby; Murdiningrum, Yustiana Ambarini (UI Scholars Hub, 2012)
This paper investigates how the potential of the newly enacted village forest policy to improve the welfare of local people and examines how different actors at local level perceive a legal framework suitable for improving the welfare of local people and enhancing local development. We conducted research through in-dept interviews involiving 75 respondents from different actors, such as policy makers, politician, village chief, customary chief and villagers. The research establish that forest policy on village forestry was a good option for local people to improve their welfare; however, litle understanding of the substance of the newly village forest policy of local development actors due to limited public consultation undertaken at district and village level would become a real challenges for executing the policy. The work of the policy is also depend on the extent to which the central goverment is capable of undertanding local context where multiple legal system operates.